Determination of Communication in the Organization: Non Verbal, Oral and Written (Literature Review) - Kurniadi, Wahyu; M. Ridho Mahaputra (Journal of Law, Politic and Humanities, 2021)
Literature review article on the influence of non-verbal, oral and written on communication is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of communication science in organizations. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Non-verbal influences on communication; 2) Oral effect on Communication; and 3) Writing has an effect on Communication. Apart from these 3 exogenous variables that affect the endogenous variable Communication, there are still many other factors including the Competence, Environment and Skill variables.